Ring-opening polymerization behavior of l-lactide catalyzed by aluminum alkyl catalysts - Yoo, Ji Yun; Kim, Youngjo; Ko, Young Soo (Journal of industrial and engineering chemistry (Seoul, Korea), 2013)
The l-lactide polymerization using trimethylaluminum (TMA), triethylaluminum (TEAL), trioctylaluminum (TOA), triisobutylaluminum (TIBA), and aluminum isopropoxide (Al(O-i-Pr)3) were studied to produce a PLA. The conversion, turnover frequency (TOF), and molecular weight of TIBA were higher than those of Al(O-i-Pr)3 with the polymerization time of 5min. In the case of 15min, the conversion of aluminum alkyls was lower than that of Al(O-i-Pr)3, but the molecular weight of PLA produced by aluminum alkyl was relatively high in comparison with the catalytic activity of Al(O-i-Pr)3. TMA, TEAL, and TIBA seemed to have lower propagation rates and much lower termination rates than Al(O-i-Pr)3.